Prawo do bezpieczeństwa w obliczu zmian klimatycznych. Rozważania z perspektywy prawa międzynarodowego publicznego - Adamczak-Retecka, Monika (Kwartalnik Prawa Publicznego, 2017)
One of the greatest global problems of our times is climate change. According to the United Nations, climate change and disasters involved such as draughts, floods and storms have become the direct and ongoing threat to the security of people all over the world. The main aim of this article is to point out the relationship between climate security and the enforcement of human rights, mainly the right to life, the rights to food and water and the right to environment. In particular, the correlation of climate change and economic security is analyzed. The considerations show how important the role of active individuals is and what are the responsibilities of a modern state.